Risk assessment of Q fever infection in cattle keeping pastoralist households in Kajiado County, Kenya - Peter, N.K. (University of Nairobi, 2016)
Q fever (Coxiella burnetii) is an old zoonotic disease, believed to be widely present in ruminant populations worldwide. It is an occupational disease and like many animal diseases, farm management practices are likely to have a direct impact on the presence and spread of Q fever within and between herds and to humans. The current study was conducted to assess the health risk associated with Q fever infection in pastoralist households in Kajiado County, Kenya. The study carried out was specifically: 1) to identify potential exposure pathways for Q fever infection to pastoralist household members and; 2) to estimate risk associated with Q fever infection in pastoralist individuals through the identified pathways in households with infected cattle. Data for the risk assessment were obtained from literature and a parallel sero-prevalence study conducted in three locations in Kajiado County, namely, Namanga, Mashuru, and Ngong’. These study sites were purposively selected for the study based on the availability of livestock at the time the study was conducted in the month of November to December 2013. Selection of cattle in the selected locations depended on availability of pasture and water and information provided by the local veterinarian personnel. A two-stage sampling method was used to select the villages with cattle herds in the selected locations. Eighty-four cattle herds were randomly selected in the three locations. A structured questionnaire was administered to household heads via personal interviews to collect data on their livestock management practices. Data collected on livestock management practices were used to identify the transmission pathways for Q fever infection to pastoralist household members. A qualitative risk assessment was carried out to assess the health risk associated with Q fever using the Codex Alimentarius Commission framework, which comprises of hazard identification, hazard characterization, exposure assessment and risk characterization. Two major transmission pathways, inhalation and ingestion, were identified. An event tree was constructed to show steps in the potential pathways that lead to human exposure to the pathogen, Coxiella burnetii, which causes Q fever. A risk assessment was then performed using data from the household questionnaire and secondary data from literature and other sources. The potential exposure pathways were identified including: Inhalation pathway through assisting during a reproduction event and without protection; Inhalation pathway through not cleaning/disinfecting boma/site after a reproduction event; Inhalation pathway through accumulation of animal waste/using it in the farm; and Ingestion pathway through consumption of contaminated raw milk. Risk associated with Q fever infection by pastoralist household through the identified pathways in households with infected cattle was estimated as: high in inhalation pathway through assisting during a reproduction event and without protection, and through not cleaning/disinfecting bomas/calving sites after a reproduction event; medium in inhalation pathway through accumulation of animal waste; and high, medium and low for Namanga, Mashuru, and Ngong, respectively, in ingestion of contaminated raw milk. Poor hygiene (self and that of the environment), ingestion of unpasteurized milk and its products and handling/assisting in any reproduction event without protection were among the identified steps through which the household members were exposed to the pathogen. It is recommended that awareness of the disease Q fever among pastoralists should be enhanced. This will promote reduction of environmental contamination, pathogens spread and limit the risk to the public. The community should be educated on the various symptoms of the disease and the control measures that they can practice to reduce exposure to Coxiella burnetii.